Content and construct validity of the European Portuguese A-19 Scale of Children’s Attitudes - Soares, Elsa Marta; S. Valente, Ana Rita; Leal, Gonçalo; Guitar, Barry (Revista de Investigación en Logopedia, 2023)
Stuttering is a multidimensional neurodevelopmental disorder that comprises primary and secondary behaviors but also feelings and attitudes. These ones have a huge importance in the overall characterization and impact of stuttering. This research aims to: 1) guarantee the adaptation and content validation of the assessment instrument A-19 to European Portuguese, and 2) analyze A-19 construct validity through a pilot study. Across-sectional , quantitative and qualitative study was developed to ensure the adaptation and content validation of A-19. The achievement of semantic, conceptual, experiential and idiomatic equivalences was only possible after the experts’ debate of several items concerning meaning, concept and cultural experience.The final Portuguese version of A-19  was used in a pilot study in which 42 children participated (21 children who stutter and 21 children who do not stutter). The group of school-age children who stutter presented a higher A-19 mean (6.29) in comparison with children who do not stutter (5.48), although the difference was not statistically significant. The Portuguese Version of A19 identifies the differences in feelings and attitudes between school age children who do and who do not stutter. The fact that this sample of children who stutter is already attending speech and language therapy sessions in which emotional, behavioural and cognitive reactions are explored, may have contributed to a non-significative difference in A-19 scores.  The content and construct validity of A-19 European Portuguese Version is assured, as so this is a valid instrument to assess feelings and attitudes of school age children who stutter.
Keywords: Assessment; Cross-cultural; Feelings and attitudes; School-age children; Stuttering